Lipid oxidation and sensory characterization of Omega-3 rich buffalo burgers enriched with chlorogenic acids from the mate (Ilex paraguariensis) tree harvesting residues. (September 2021) - Heck, Rosane Teresinha; da Rosa, Jordana Lima; Vendruscolo, Raquel Guidetti; Cichoski, Alexandre José; Meinhart, Adriana Dillenburg; Lorini, Alexandre; Paim, Bruna Trindade; Galli, Vanessa; Robalo, Silvino Sasso; Dos Santos, Bibiana Alves; de Pellegrin, Luis Fernando Vilani; de Menezes, Cristiano Ragagnin; et al.
Abstract: A freeze-dried extract from the bark of mate branches (BMBE) containing high chlorogenic acids (CGA) content (30 g 100 g −1 ) was produced. Then, chia oil was mixed with 7.5% BMBE and sonicated for 0, 10, and 20 min. Chia oil with or without the addition of BMBE was hydrogelled and used to produce buffalo burgers with 50% reduction in animal fat. CGA levels and the nutritional, oxidative, and sensory properties of the burgers were analyzed. A reduction of 30% fat and an increase above 60% PUFA/SFA ratio was observed for the reformulated raw and cooked burgers. In addition, the Omega-6/Omega-3 PUFA ratio of the burgers decreased from 20.8 (raw) and 31.9 (cooked) to values lower than 2. The addition of BMBE enriched the burgers with CGA, preventing an increase in lipid oxidation caused by chia oil. The addition of BMBE-enriched hydrogelled chia oil not subjected to sonication did not affect the sensory properties of the burgers. Highlights: We produced an extract using a residue from the yerba mate cultivation (BMBE). The freeze-dried extract presented 30 g 100 g −1 of chlorogenic acids (CGA). Chia oil enriched with BMBE was gelled and applied as a fat replacer in burgers. The addition of BMBE enriched the burgers with CGA. BMBE addition retarded the increase in TBARS values caused by chia oil.